The Relationship between Expression of p70s6k with Radiotherapy Response in Cervical Cancer - I. Kurnia; B. Siregar; Z. Alatas; I. Ramli; T. Kurjana; A. Andriono; M.D.L. Tobing; B.S. Hernowo; T. Kisnanto; Y. Lusiyanti; D. Tetriana; S. Soetopo (PPIKSN-BATAN, 2016)
There are many important prognostic factors in advanced stage cervical cancer primary treated with radiotherapy. Besides clinical factors, many biomarkers have been studied in relation with radiotherapy response. The p70s6k is a biomarker which plays a significant role in cell proliferation. Increased levels of p70s6k are also associated with drug resistance in cancer. In the present study, the relationship between the expression level of p70s6k before treatment and the radiotherapy response in cervical cancer was determined. Immunohistochemical staining of p70s6k, MIB-1, and p53 was conducted in microscopic slide from 21 cancer tissue biopsies before treatment with radiotherapy. After the treatment had completed early radiotherapy response was observed by pelvic control method. The results showed that p70s6k is partly highly expressed (61.9%, 13/21) and partly low expressed (38.1%, 8/21) in the cancer cells. They also show that there is no statistically significant differences on AgNOR mean, MIB-1, and p53 indices in the different degrees of p70s6k expression (p≥0.05). Higher expression levels of p70s6k is more strongly associated with good radiotherapy response compared to lower ones (p=0.05). In conclusion, the level of p70s6k expression before treatment has an association with radiotherapy response.